Post-operative Analgesia from Preemptive to Preventive Approach: Evolution and Clinical Implications - Abodonya, Ahmed (Asian Journal of Pharmaceutics (AJP), 2025)
Pain management has shifted from a reactive approach to a proactive strategy focused on prevention. This study analyzes the development, neurophysiological foundation, and clinical uses of preemptive and preventive analgesia in the perioperative setting. Regardless of advancements in analgesic approaches, post-operative pain is frequently insufficiently managed in numerous sufferers, with more than 80% experiencing moderate-to- severe discomfort and up to 50% developing chronic pain after specific procedures. The shift from preemptive analgesia (interventions before surgical incision) to preventative analgesia (interventions during the perioperative phase) signifies our improved comprehension of pain processes. This article examines pain assessment tools, technological advancements, and evidence-based methodologies for implementing efficient perioperative pain management procedures. Multimodal strategies integrating pharmacological treatments, regional anesthesia procedures, and personalized care plans demonstrated substantial enhancements in patient outcomes, such as diminished pain severity, reduced opioid usage, and a lower occurrence of chronic postsurgical pain. Future directions highlight individualized analgesic regimens, the use of artificial intelligence, and ongoing research into innovative treatment strategies to optimize pain management and improve post-operative recovery.